A systematic review and meta-analysis of short- and long-term complications of early versus delayed penile prosthesis implantation in patients with ischemic priapism - Agustin J. Nanda De Niro; Gede Wirya Kusuma Duarsa; Marshal Harvy Wicaksono; Pande Made Wisnu Tirtayasa; Kadek Budi Santosa; I Wayan Yudiana; Nyoman Gede Prayudi (Archivio Italiano di Urologia e Andrologia, 2024)
Background: This study determined pooled estimates of short- and long-term complications of early versus delayed implantation of penile prosthesis in patients with ischemic priapism. Methods: We searched Pubmed, ProQuest, Scopus, EBSCOHost, and other sources from January 1, 2013, to March 2023. All study designs were included except animal studies, review articles, and consensus documents. Of the 214 articles, four studies were included in the systematic review, and further meta-analysis included three studies (PROSPERO CRD42023411005). Results: The short-term complication rate was lower with early implantation than with later implantation (β= -2.08; 95% Confidence Interval [CI] = -3.54, -0.6; p = < 0.05). A similar value was also found in the pooled analysis for long-term outcomes, defined as overall satisfaction rate, which is better with early implantation than later (β = 2.18; 95% CI = 1.35, 3.02; p= < 0.05). Conclusions: The results of the pooled analysis confirmed that short-term complications were significantly lower with early implantation than with delayed implantation. Overall satisfaction rates were higher in early implantation than in delayed implantation of penile prostheses.